A Positive Communication–Based Family Counseling to Prevent Mental and Reproductive Health Problems among Adolescents: Konseling Keluarga Berbasis Komunikasi Positif untuk Mencegah Masalah Kesehatan Mental dan Reproduksi pada Remaja - KASPIRAYANTHI, NI KETUT DEVY (STIKES Advaita Medika Tabanan, 2026)
Abstract Remaja merupakan periode transisi yang rentan terhadap masalah kesehatan mental, perilaku berisiko seperti penyalahgunaan zat, seks pranikah, dan pernikahan dini, yang sangat dipengaruhi oleh kualitas dukungan dan komunikasi dalam keluarga. Berbagai studi terkini menunjukkan bahwa konseling keluarga dan komunikasi orang tua–remaja yang positif berperan penting dalam menurunkan kecemasan, depresi, perilaku adiktif digital, serta meningkatkan perilaku kesehatan reproduksi remaja. Artikel ini bertujuan mendeskripsikan model konseling keluarga berbasis komunikasi positif untuk memperkuat peran keluarga dalam pencegahan masalah kesehatan mental dan reproduksi pada remaja. Metode yang diusulkan adalah pengabdian masyarakat berupa edukasi kesehatan, pelatihan komunikasi positif, dan sesi konseling keluarga berkala dengan melibatkan remaja dan orang tua. Diharapkan intervensi ini meningkatkan pengetahuan keluarga tentang kesehatan reproduksi remaja, memperbaiki kualitas komunikasi, dan menurunkan faktor risiko psikososial remaja. Kata kunci: konseling keluarga, remaja, komunikasi positif, kesehatan mental, kesehatan reproduksi. Abstract Adolescents are in a critical transitional phase and are highly vulnerable to mental health problems and risky behaviors, including substance abuse, premarital sexual activity, and early marriage. These issues are closely related to inadequate family support and ineffective communication between parents and adolescents. Recent evidence highlights the effectiveness of family counseling and positive parent–adolescent communication in reducing anxiety, depression, digital addictive behaviors, and in promoting healthy reproductive behaviors among adolescents.This grant proposal aims to develop and implement a family counseling model based on positive communication to strengthen family capacity in preventing mental and reproductive health problems among adolescents. The program will be conducted as a community-based intervention comprising reproductive health education, positive communication skills training for parents and adolescents, and structured family counseling sessions delivered periodically. The expected outcomes of this program include increased family knowledge of adolescent mental and reproductive health, improved quality of parent–adolescent communication, reduced psychosocial risk factors, and enhanced protective behaviors among adolescents. This program is expected to contribute to sustainable family-based prevention efforts and support national adolescent health promotion initiatives Keywords: family counseling, adolescents, positive communication, mental health, reproductive health.Top of Form